Targeted delivery of BDNF-loaded poly (lactide-co-glycolide) nanoparticle to the brain: penetration through blood brain barrier and neuroprotective effect in stroke / Siti Norsyafika Kamarudin - Kamarudin, Siti Norsyafika (2019)
Stroke remains a major public health burden in Malaysia due to high morbidity and mortality. Neuroprotection by Brain derived neurotrophic factor (BDNF) has the potential to minimise the ischemic damage and theoretically improve freedom from disability among stroke survivors. There is a need to develop nanoparticle (NP) drug delivery system to deliver BDNF following intravenous route after the ischemic insult due to poor penetration to the brain. In this study we proposed to design BDNF-loaded poly (lactide-co-glycolide) (PLGA) nanoparticles (BDNF-NPs) and to study neuroprotective effect of BDNF on permanent middle cerebral artery occlusion (pMCAO) model of ischemia in rats. BDNF containing PLGA nanoparticles were synthesized using water/oil/water (W/O/W) double emulsion solvent evaporation method. The nanoparticles were characterized for particle size (PS) and zeta potential (ZP) using a dynamic light scattering (DLS) technique. The percentage entrapment efficiency (%EE) was calculated. Penetration of blood brain barrier (BBB) was studied using an in vitro model employing human brain microvascular endothelial cells (HBMECs). The PS and ZP of NPs were found to be 186.6 nm and -18.6 mV respectively with 93% EE. Confocal laser scanning microscopy (CLSM) confirmed penetration and distribution of fluorescent NPs using Coumarin 6 as fluorescent probe into HBMECs and the number of NPs entering the cells was measured. Apolipoproteins (Apo) role in the NP uptake was investigated using ApoE, B100, A1 or C2, incubated with HBMECs. Cell viability was determined using MTS-assay. BDNF release into cells was quantified using ELISA method. No cytotoxicity of Apo-coated/non-coated PLGA NPs was observed. The fluorescent intensity was found to be significantly higher for ApoE-coated NPs compared to ApoA1-coated NPs (1.31 folds, p<0.001) and control, not coated NPs (4.06 folds, p<0.001). The fluorescent intensity of ApoB100-coated NPs was significantly higher compared to control group by 3.88 folds (p<0.001). Significantly higher concentration of BDNF was found in HBMECs after treatment with Apo E- and Apo B100-coated NPs compared to control group by 69.31 (p<0.001) and 57.46 folds (p<0.001) respectively. The final step was to test neuroprotective effect of BDNF-NPs on pMCAO model of ischemia in rats. Sprague-Dawley rats were divided into 4 groups of 7 rats each. Group 1 was subjected to sham operation, group 2, 3 and 4 were subjected to pMCAO. Four hours after pMCAO, group 3 and 4 were intravenously treated with BDNF and BDNF-NPs respectively. Functional outcome was assessed at 2 h and 24 hours after pMCAO using modified Neurologic Severity Score (mNSS), rotarod and grid walking. Rats were sacrificed by terminal cardiac puncture, blood was taken for assessment of neurobiomarkers (NSE and S100β) level and brain was subjected for infarct area assessment and volume measurement. BDNF-NPs treated group showed significant improvement in mNSS when compared with pMCAO and BDNF treated groups demonstrating decreased mNSS score by 2.0 and 2.0 times. BDNF-NPs treated group showed improved rotarod performance by increasing latency time on rotarod by 2.44 (p<0.001) and 2.76 folds (p<0.001) when compared with pMCAO and BDNF treated groups. The infarct volume in rats treated with BDNF-NPs was significantly smaller by 1.91 and 1.95 folds (p<0.001) when compared with pMCAO and BDNF treated groups. The results were further corroborated by the estimation of neurobiomarkers (NSE and S100β) level. Overall, BDNF loaded PLGA nanoparticle is a promising drug formulation that act as neuroprotective agent in ischemic stroke model.